R&D Embodied Technological Change, Producers - Users Interaction, and Productivity at the Firm Level: A Germany-Italy Comparison - Enrico Santareli; Francesca Lotti (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1998)
This paper follows a knowledge production function approach to assess the contribution of R&D spending, the purchase of new machinery, and producers-users interaction to the productivity performance of German and Italian firms in manufacturing. For this purpose it employs micro-aggregated data from the First Community Innovation Survey. The regression analysis confirms the results of previous studies that technological change embodied in new machinery and capital equipment is a major factor affecting the productivity level of manufacturing firms in most industries (in particular in Italy), although the role of R&D activities is crucial for most firms in both countries, and that this is also the case in traditional consumer goods industries such as textiles, clothing, and leather & leather products. Conversely, only for Germany does producers-users interaction prove significantly to influence the productivity level of firms in certain industries.
Keywords: 330